Destination Rio - Acclimatisation: General aspects - Gianfelici, A. (EWF Scientific Magazine, 2016)
Organising a number of important sporting events in cities and countries that are in time zones different to one's own, has in the past been the focus of attention of many experts regarding the issues that this condition could pose. Starting from the problems that arose around the Olympic Games in 1968 in Mexico City, or the work undertaken for the Olympic Games in Atlanta, Sydney and even more recently for those of Beijing 2008. In this regard, the Institute of Sports Sciences and Medicine of the Italian National Olympic Committee, produced a document that addressed the problems of acclimatisation, climatic conditions, health risks, even the problems of air pollution that the delegation of Italian athletes might have faced during their Olympics experience. With Rio having been appointed to host the next Olympic Games, the European National Olympic Committees once again face a challenge regarding any issues related to the trip. The overall focus includes many aspects, ranging from logistics to the minor aspects such as currency exchange, car rental and similar issues, but also engaging in and performing all their sports activities in the safest way possible. This short vademecum does not expect to solve all possible problems, nor to give information on all aspects of the trip, it is simply a memorandum of the physiological aspects related to acclimatisation. WEATHER CONDITIONS The 10,500 athletes expected at the Games in Rio will compete in a vast area around the bay of Rio where the weather may differ from one location to another. The various websites providing information about the climate and meteorological aspects show small differences. In order to predict the approximate climate in Rio in August 2016, we have used www.wunderground. com, analysing the climate over the last eight years, on days 5 to 21 August. A data analysis has provided us with general indications that pay particular attention to the possible and varied situations. There are days when the daily maximum temperature varies between 19 and 35°C, with an average of 26.4°C, while at night the temperature can drop to 12°C. One factor to be considered will be the possibility of high levels of humidity, which we know increase the perception of heat, as it makes evaporation of water contained in sweat more difficult. In comparison with the maximum temperatures and humidity recorded in the previous editions of the Olympic Games, we therefore expect an acceptable temperature (when we think of 32-33°C in Atlanta!), but with a considerably higher humidity rate. Since this is also the Southern Hemisphere, we must also take into account that it will still be the winter season and there is a chance of rain. The same analysis shows that four of the sixteen days of the competition could be marked by rain. For those wishing to make an more in-depth study into the perception of heat as opposed to the different weather conditions and climates that they will encounter (temperature, humidity, solar radiation, wind speed), but also considering the anatomical structure of the athlete, the type of clothing to wear, exercise intensity required, there is a simple and useful application called RayMan, available for free on the Internet.